ICASSP '84. IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1984.1172751
|View full text |Cite
|
Sign up to set email alerts
|

Improved hidden Markov modeling of phonemes for continuous speech recognition

Abstract: This paper discusses the use of the Hidden Markcv Model (HMM) in phonetic recognition. In particular, we present improvements that deal with the problems of modeling the effect of phonetic context and the problem of robust pdf estimation. The effect of phonetic context is taken into account by conditioning the probability density functions (pdfs) of the acoustic parameters on the adjacent phonemes, only to the extent that there are sufficient tokens of the phoneme in that context.This partial conditioning is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…It has been found that due to co-articulation effects, the beginning and end of a phone have been modified by the previous & next phone. Therefore, context dependence of phones [6] is a feature which brings down the efficiency of ASRs due to resulting acoustic variations of phonetic units. So the context dependent variations should be modeled.…”
Section: Continuous Speech Recognitionmentioning
confidence: 99%
“…It has been found that due to co-articulation effects, the beginning and end of a phone have been modified by the previous & next phone. Therefore, context dependence of phones [6] is a feature which brings down the efficiency of ASRs due to resulting acoustic variations of phonetic units. So the context dependent variations should be modeled.…”
Section: Continuous Speech Recognitionmentioning
confidence: 99%
“…The approach is not novel, see [4], and it is likely suboptimal but we prefer it to DT AMs for ease of implementation in MapReduce.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%
“…Context-dependent models have been shown to be superior to context-independent phone models (e.g. [1,12,8]). However, as context-dependent modeling results in a great increase in the number of parameters to train, methods have to be found to prevent the use of undertrained models.…”
Section: Introductionmentioning
confidence: 99%
“…Among context-dependent models, triphones, which model both left and right contexts, have been shown to be successful in modeling contextual phonetic variations (e.g. [12,7,3]). …”
Section: Introductionmentioning
confidence: 99%